2015
DOI: 10.3389/fpls.2015.00602
|View full text |Cite
|
Sign up to set email alerts
|

The novel and taxonomically restricted Ah24 gene from grain amaranth (Amaranthus hypochondriacus) has a dual role in development and defense

Abstract: Grain amaranths tolerate stress and produce highly nutritious seeds. We have identified several (a)biotic stress-responsive genes of unknown function in Amaranthus hypochondriacus, including the so-called Ah24 gene. Ah24 was expressed in young or developing tissues; it was also strongly induced by mechanical damage, insect herbivory and methyl jasmonate and in meristems and newly emerging leaves of severely defoliated plants. Interestingly, an in silico analysis of its 1304 bp promoter region showed a predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 94 publications
(111 reference statements)
0
21
0
Order By: Relevance
“…Cultivation procedures for the germination, growth and maintenance of wild type (WT) and transgenic OE A . thaliana plants under controlled growing conditions were performed as described previously [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cultivation procedures for the germination, growth and maintenance of wild type (WT) and transgenic OE A . thaliana plants under controlled growing conditions were performed as described previously [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…hypochondriacus plants were subjected to salt and water-deficit stress to confirm the induced expression of the AhERF and AhDof genes observed in silico . The experiments were performed in a growth chamber under controlled conditions of light (photosynthetic photon flux density ≈ 300 μmol m -2 s -1 ) and temperature (28°C, 16 h light/ 8 h dark), as described previously [ 14 , 15 , 33 ]. Leaf and root samples were collected at different after being exposed for different time periods (i. e, 2 to 8 days) to the stress conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that the WDS response in Ahypo roots included the accumulation of osmolytes and increased levels of ROS scavenging and heat shock proteins, together with the induction of certain TFs (Huerta-Ocampo et al , 2011). Several other amaranth genes have been subsequently proposed as possible contributing factors to increased tolerance against several (a)abiotic stresses in grain amaranth, including an orphan gene (Massange-Sánchez et al , 2015), a gene with an unknown function domain (Palmeros-Súarez et al , 2017) and various TF genes (Palmeros Súarez et al , 2015; Massange-Sánchez et al , 2016). The above genes were induced in grain amaranth by several stress conditions and frequently conferred stress tolerance when overexpressed in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%